Quebec Labour and the Referendums - Savage, Larry (Canadian Journal of Political Science/Revue canadienne de science politique, 2008)
The Quebec labour movement's decision to withdraw its support for Canada's federal system in the 1970s and instead embrace the sovereignist option was unquestionably linked to the intersection of class and nation in Quebec. In this period, unions saw the sovereignist project as part of a larger socialist or social democratic societal project. Because the economic inequalities related to ethnic class, which fuelled the labour movement's support for sovereignty in the 1970s, were no longer as prevalent by the time of Quebec's 1995 referendum, organized labour's continued support for the sovereignist option in the post-referendum period cannot adequately be explained using the traditional lens of class and nation. This paper employs an institutional comparative analysis of Quebec's three largest trade union centrals with a view to demonstrating that organized labour's primary basis for supporting sovereignty has changed considerably over time. While unions have not completely abandoned a class-based approach to the national question, they have tended to downplay class division in favour of an emphasis on Quebec's uniqueness and the importance of preserving the collective francophone identity of the nation. Party–union relations, the changing cultural, political and economic basis of the sovereignist project and the emergence of neoliberalism in Quebec are offered as key explanatory factors for the labour movement's shift in focus.